Semarang Mall and Communal Space by Cultural Values Empowerment - Nova Dimas Saputra (Jurnal Poster Pirata Syandana, 2023)
The Final Project with the title "Semarang Mall and Communal Space by Cultural Values Empowerment" has the Architectural Programming (LP3A) as one of the stages in the Final Project series. The methods used in this Architectural Programming are literature studies, field observations, comparative studies, and interviews. The title of this Final Project is based on the high economic needs in Semarang City so that a shopping center is still needed. On the other hand, the fading of cultural values due to the effects of modernization is a problem that must be considered, so that cultural values can be preserved again. In addition, there are supporting facilities such as communal spaces that can accommodate various user activities, so that more and more types of activities can be carried out in this shopping center area and become an advantage compared to other malls in Semarang City. The planning site of this Final Project will be located on Jl. Patimura, Rejomulyo, Semarang Timur District, Semarang City, Central Java. This site is worthy of establishing a mall or shopping center because of its strategic location and supports the concept of cultural values, because it is next to the Kota Lama Museum and adjacent to the Kota Lama Semarang area. Departing from the problem of fading cultural values, the building to be designed must have strong cultural elements to be able to resurface existing local cultural entities. The material for finishing the building will use local materials such as wood and stones. Therefore, the application of the concept of cultural value will be implemented using the concept of Neo-Vernacular architecture. The use of the concept of Neo-Vernacular can bring elements of culture without losing the modern impression that is favored by many people today. Collaboration between cultural elements and modern buildings is still very rarely found, especially in the city of Semarang, so it is a great potential to be able to attract the attention of many people.